Compressive resistance level effect on impact performance of fi-ber reinforced concrete - Vivas Montes, Juan Carlos (2022)
Impact resistance represents a key property of fiber reinforced concrete (FRC). To study this property, a test method was recently proposed; which consists in repeated drops of a projectile on simply supported prisms, and allows to evaluate FRC behavior both at cracking and after cracking. With the aim of verifying the sensitiveness of this method, this paper analyzes the influence of the compressive strength of the FRC matrix on each parameter of the impact test. Three FRC incorporating 30 kg/m3 of hooked-end steel fibers were prepared, varying the water/cement ratio (0.59, 0.50 and 0.43). It was found that although only small effects on the cracking energy were observed as the concrete compressive strength increases, the post-cracking energy increased in a greater proportion. However, the cracking growth rate, an impact pa-rameter strongly sensitive to the type and content of fibers, remained practically constant for different compressive strength levels.